(untitled) (IITM Journal of Business Studies, 2024)
The book is written in the English language. The average time taken to read a chapter was one hour and 45 minutes. Gender bias and color bias has always been a critical social evil in degrading humanity and equality. It has lead to social injustice and curbing of creativity and talent of masses. The creative and hardworking skilled women of color are not acknowledged and appreciated for their work which develops resentment and anger amongst themselves in many countries. Since, diversity is the soil of our mother Earth; we must stand together for an empowered future.Why She Must Lead shares Dr Vasudha Sharma’s personal story of immigrating to the United States from India fifteen years ago after her marriage, looking for healthier opportunities. She interviews many women who play a vital part in raising questions and forming solutions regarding the leadership gap. It is a factual reflection of her evolution into the non-profit world from a serial entrepreneur. The book is an assemblage of all aspects of resourceful thoughts that women of color require to be unbeaten in today’s scenario. Vasudha has done a thorough study through her personal experience and stories from women leaders. This study can inform the readers with a broader perspective of work-life experiences of women of color. Inspired by people she has met around the world, Dr Vasudha has given solutions in her book where issues like the pay gap, broken rungs, and lack of mentorship can be filtered out methodically, and workplaces can act to raise the most underrepresented group of women. The book is flowing in two hundred and forty six pages and across all the pages, Dr Vasudha talks about fears, pain, and challenges with empathy and humility. She inspires the women of color to challenge the assumptions and myths and lead and live with a mission.